The Role of Nutrients in Supporting The Immune System Against Viral Infection; Newly Emerged Coronavirus (COVID19): A Narrative Review - Farag, Halgord Ali; Rafat Baqi, Hardi; Hussein, Yousif Taha; Hamid Shareef, Osama; Ahmed Qadir, Syamand; El Afifi, Amany; Hamid El Bilbeisi, Abdel (Kurdistan Journal of Applied Research, 2020)
Balanced nutrition is vital for peak performance of immune function, especially when a global pandemic is emerging, and there is major lack in approved treatments for it. Many nutrients and their abundance in cells induce immune function. We performed a narrative review to describe existing literature with regard to role of nutrients in supporting the immune system against viral infection including coronavirus (SARS-COV-2). PubMed, Scopus and Google Scholar databases were searched for relevant articles. This review represents a picture of the current state of the art. In particular, we classified the nutrients by means of their types, abundance, importance and possible antiviral effects in immune system. The macronutrients such as carbohydrates, lipids, and proteins are essential for cells to generate energy and participate in immune function as well. However, unbalanced diet with high levels of macromolecules could lead to chronic diseases that impair the body’s immune abilities. The micronutrients including vitamins and minerals participate in immune system on a bigger scale that almost all body’s immune mechanism depends on the expressions of micronutrients. Vitamins improve immune responses. Some vitamins include A, D, K, B, and C enroll in antiviral mechanism of the immune cells. A group of trace elements including zinc, copper, selenium, magnesium, manganese, and iron are heavily contributed in maintaining body’s immunity. The susceptibility toward the infectious diseases is highly elevated in cases of their deficiencies. Besides their antiviral roles, vitamins such as E and C with minerals in the cells adopt antioxidant properties that help immune cells to fight oxidative stress in the cells. Nevertheless, the high levels of minerals such as iron could threat the immune system by growing the oxidative stress. So, maintaining rich and balanced nutrition could improve body’s immune function, and possibly prevent viral infections including COVID-19.